ANALISIS PENERAPAN OFFICIAL ASSESMENT SYSTEM DALAM PENERIMAAN PAJAK BUMI DAN BANGUNAN PADA KANTOR BADAN PENDAPATAN DAERAH KABUPATEN KONAWE SELATAN - Jaya, Asnan; Muthalib, Abd. Azis; A.Sabilalo, Mahmudin (JITAA : Journal Of International Taxation, Accounting And Auditing, 2023)
This research aims to analyze the implementation of the official assessment system in land and building tax revenue at the Regional Revenue Office of South Konawe Regency. Data collection was carried out using observation, interviews, and documentation techniques. The researcher used source triangulation to check the validity of the research data. Data analysis in this study employs three components consisting of data reduction, data presentation, and conclusion drawing. The results of the study indicate that: (1) The Regional Revenue Office of South Konawe Regency has implemented the official assessment system in land and building tax revenue effectively. (2) The factors that become obstacles/challenges in the implementation of the official assessment system include lack of understanding, access difficulties, technical disruptions, regulatory changes, and financial limitations. (3) Strategies to overcome the obstacles/challenges in the implementation of the official assessment system include socialization and education, improving technical services, investing in adequate software, better data management, alternative payments, education and assistance, payment relief, improving accessibility, and enhancing communication with taxpayers.